Preparation method of polytetrafluoroethylene ultra-fine filaments

By combining the mixture of modified cordierite fibers and nanobarite with modified polyparabenzamide fibers and combined with multi-step process processing, the problem of insufficient performance in the preparation of existing polytetrafluoroethylene fibers was solved, and polytetrafluoroethylene ultrafine filaments with high fracture strength and uniform dryness were prepared.

CN119332365BActive Publication Date: 2025-03-07SHANDONG SENRONG PLASTIC IND TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411879630.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-07
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

In the existing preparation methods for polytetrafluoroethylene fibers, the product has a high dryness rate and low fracture strength, and structural defects are easily generated during the production process, which affects performance.

Method used

The mixture of modified cordierite fibers and nanobarite is combined with modified polyparabenzamide fibers, and polytetrafluoroethylene ultrafine filaments are prepared by maturation, blanking, extrusion, calendering, deoiling, stretching, thermal drafting, twisting and heat setting.

Benefits of technology

The breaking strength of the polytetrafluoroethylene ultra-fine filaments is significantly improved, the unevenness of the strip dryness and elongation of the break are reduced, and the mechanical properties of the fibers are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of polytetrafluoroethylene material preparation, and specifically relates to a method for preparing polytetrafluoroethylene ultrafine filaments. The preparation method comprises the following steps: (1) preparing a mixture of modified cordierite fiber and nano-baryte; (2) preparing modified polyparabenzamide fiber; (3) preparing a modified polytetrafluoroethylene film; (4) preparing polytetrafluoroethylene ultrafine filaments. The method for preparing polytetrafluoroethylene ultrafine filaments of the present invention selects a mixture of modified cordierite fiber and nano-baryte, and a modified polyparabenzamide fiber and a polytetrafluoroethylene dispersion resin for compounding, thereby ensuring the breaking strength of the prepared polytetrafluoroethylene ultrafine filaments and reducing their unevenness and elongation at break.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polytetrafluoroethylene material preparation, and specifically relates to a method for preparing polytetrafluoroethylene ultrafine filaments. Background Art

[0002] Polytetrafluoroethylene has excellent chemical stability, heat resistance, cold resistance, chemical corrosion resistance, and also has good insulation, hydrophobicity, lubricity, flame retardancy, atmospheric aging resistance, high and low temperature adaptability and good mechanical properties. At present, the main production methods of polytetrafluoroethylene fiber are emulsion spinning, paste extrusion spinning, film splitting spinning and melt spinning. Among them, emulsion spinning is the main method currently used in industry. A polytetrafluoroethylene emulsion (concentration of 60%) with an average molecular weight of about 3 million and a particle size of 0.05 mm is mixed with fiber carriers such as viscose or polyvinyl alcohol to make a spinning solution, and then the carrier is carbonized and removed at high temperature, and the polymer is sintered to continuously form fibers. However, structural defects are easily generated during the sintering process, the strength is low, the fineness is small, and the product is brown. The paste extrusion spinning method is to mix PTFE powder and volatile substances into a paste, extrude it through a screw, and then spin it into strip-shaped fibers through a narrow slit spinneret. Then, a needle roller is used for fibrillation treatment to obtain fibers with higher strength and larger fineness. This method produces a large amount of volatile substances during the production process, which need to be treated and are not conducive to environmental protection. The melt spinning method is to melt the copolymer of tetrafluoroethylene and 4-5% perfluoroethylene and perfluoropropyl ether and then spin it to obtain fibers with higher strength. The film splitting spinning method is to press the polytetrafluoroethylene powder, sinter it to obtain a cylinder, cut or cut it to obtain a film, cut it into strips, and then perform heat stretching and other treatments to obtain white fibers.

[0003] The Chinese patent application number 200610056793.4 discloses a high-strength polytetrafluoroethylene fiber and its manufacturing process. The processing technology is as follows: ① Mixing polytetrafluoroethylene high-pressure dispersion material with lubricating oil; ② Pre-pressing the mixture into a molded product; ③ Extruding the molded product into a monofilament; ④ Degreasing, sintering, and drawing the monofilament to complete the finished product. This method has become a typical polytetrafluoroethylene paste extrusion spinning method. Although it is simple and easy to operate, the polytetrafluoroethylene monofilament obtained has the defects of poor uniformity and low strength. Therefore, it is necessary to explore a new method for preparing polytetrafluoroethylene ultra-fine filaments. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing polytetrafluoroethylene ultrafine filaments. The polytetrafluoroethylene ultrafine filaments prepared by the method have high breaking strength, low yarn unevenness and low breaking elongation.

[0005] The method for preparing the polytetrafluoroethylene ultrafine filaments of the present invention comprises the following steps:

[0006] (1) cordierite fiber, nano-baryte and anhydrous ethanol are uniformly mixed to prepare a suspension, and then heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane are added and mixed for 65-70 minutes, and finally ball milled, dried and sieved to prepare a mixture of modified cordierite fiber and nano-baryte;

[0007] (2) mixing poly(p-phenylene sulfoxide) with dimethyl sulfoxide to prepare a poly(p-phenylene sulfoxide) fiber dispersion, and then freeze-drying the mixture to prepare a pretreated poly(p-phenylene sulfoxide) fiber, adding toluene, acetic acid and phenyltriethoxysilane coupling agent to the pretreated poly(p-phenylene sulfoxide) fiber, reacting the mixture at 70-75° C. for 7.5-8 hours, and finally drying the mixture to prepare a modified poly(p-phenylene sulfoxide) fiber;

[0008] (3) mixing polytetrafluoroethylene dispersion resin, a mixture of modified cordierite fiber and nano-barite, modified polyparabenzamide fiber, No. 5 aviation kerosene and Isopar M solvent oil, and then sequentially performing aging, pressing, extrusion and calendaring treatments to prepare a modified polytetrafluoroethylene-based membrane;

[0009] (4) The modified polytetrafluoroethylene based film prepared in step (3) is deoiled at 285-290° C., then stretched, and cut into polytetrafluoroethylene flat filaments. Finally, the polytetrafluoroethylene flat filaments are heat-drawn, twisted, and heat-set to prepare polytetrafluoroethylene ultrafine filaments.

[0010] in:

[0011] In step (1), the mass ratio of cordierite fiber to nano-baryte and to anhydrous ethanol is 1:25.

[0012] In step (1), the mass ratio of cordierite fiber to nano-baryte is 1:0.6-0.8.

[0013] In step (1), the cordierite fiber, nano-barite and anhydrous ethanol are uniformly mixed, specifically stirred at a speed of 500 r / min for 70-80 min, and then ultrasonically dispersed for 35-40 min at an ultrasonic power of 50 W.

[0014] In step (1), the mass ratio of heptadecafluorodecyltrimethoxysilane to γ-aminopropyltriethoxysilane is 3:1.

[0015] In step (1), the total mass of heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane accounts for 2-3% of the total mass of cordierite fiber and nano-bite.

[0016] The ball milling, drying and sieving in step (1) specifically comprises ball milling the slurry obtained after mixing in a ball mill for 40-45 minutes, then drying at 75-78° C. for 4.5 hours, and finally passing through a 250-mesh sieve.

[0017] In step (2), the mass volume ratio of polyparabenzamide fiber to dimethyl sulfoxide is 1:2.8, expressed in g / mL.

[0018] The mixing in step (2) is stirred at room temperature for 28 hours, and the freeze-drying is freeze-dried at -45°C for 50 hours.

[0019] In step (2), the mass of the phenyltriethoxysilane coupling agent is 2.4% of the mass of the pretreated polyparabenzamide fiber. Acetic acid is added to adjust the pH value of the reaction system to 5. The mass ratio of the pretreated polyparabenzamide fiber to toluene is 1:20.

[0020] The drying temperature in step (2) is 120° C. and the drying time is 3.5 h.

[0021] In step (3), the mass of the mixture of modified cordierite fiber and nano-baryte accounts for 2.2-2.8% of the mass of the polytetrafluoroethylene dispersion resin, the mass of the modified polyparabenzamide fiber accounts for 3.5-4.3% of the mass of the polytetrafluoroethylene dispersion resin, the mass of No. 5 aviation kerosene accounts for 6% of the mass of the polytetrafluoroethylene dispersion resin, and the mass of Isopar M solvent oil accounts for 18% of the mass of the polytetrafluoroethylene dispersion resin.

[0022] The manufacturer of Isopar M solvent oil in step (3) is ExxonMobil.

[0023] The aging, pressing, extrusion and calendering treatment in step (3) is specifically aging at 65-70°C for 55 hours, pressing the aging raw material into a columnar blank at a pressure of 5 MPa, and then extruding the columnar blank into a strip, with a compression ratio of 280 and an extrusion speed of 15 m / min. Finally, the extruded strip is pressed into a polytetrafluoroethylene-based film by a calender, the pressing roller temperature is 75°C, and the calendering line speed is 10 m / min.

[0024] In step (4), the stretching temperature is 270°C and the stretching ratio is 3 times.

[0025] The width of the polytetrafluoroethylene flat filament in step (4) is 5 mm.

[0026] The temperature of the hot stretching in step (4) is 375°C and the stretching ratio is 40 times.

[0027] The twisting degree in step (4) is 450 twists / m.

[0028] The temperature of the heat setting in step (4) is 385-390°C.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The method for preparing the polytetrafluoroethylene ultrafine filaments of the present invention uses a mixture of modified cordierite fiber and nano-baryte, and a modified polyparabenzamide fiber and a polytetrafluoroethylene dispersion resin to ensure the breaking strength of the prepared polytetrafluoroethylene ultrafine filaments and reduce their unevenness and elongation at break. Among them, the addition of cordierite in the mixture of modified cordierite fiber and nano-baryte can increase the elastic modulus and the glass transition temperature of polytetrafluoroethylene and reduce the average linear expansion coefficient, while the addition of nano-baryte can increase the tensile strength and compression rebound performance of the prepared polytetrafluoroethylene. Modified polyparabenzamide fiber is a high-strength, high-modulus fiber. Its addition can ensure the breaking strength of the prepared polytetrafluoroethylene ultrafine filaments, enhance high temperature resistance, and reduce thermal shrinkage. Therefore, the mixture of modified cordierite fiber and nano-baryte is compounded with modified polyparabenzamide fiber, and within a suitable addition amount range, the prepared polytetrafluoroethylene ultrafine filament has excellent performance.

[0031] (2) In the method for preparing the polytetrafluoroethylene ultrafine filaments described in the present invention, when preparing a mixture of modified cordierite fibers and nano-barytes, heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane are used in combination to modify the modified cordierite fibers and nano-barytes, wherein the γ-aminopropyltriethoxysilane is used to improve the bonding and dispersion properties of the cordierite fibers and nano-barytes with the polytetrafluoroethylene dispersion resin, while the addition of heptadecafluorodecyltrimethoxysilane can provide additional chemical stability and low surface energy characteristics, thereby improving the mechanical properties of the prepared polytetrafluoroethylene ultrafine filaments.

[0032] (3) In the preparation method of polytetrafluoroethylene ultrafine filaments described in the present invention, there are amide polar groups in the molecular structure of polyparabenzamide fibers, but due to the presence of hydrogen bonds inside the molecular chain, it is not conducive to the exposure of polar groups, resulting in fewer surface polar groups, low chemical activity, chemical inertness of the surface, and weak interface bonding strength with polytetrafluoroethylene resin. Therefore, phenyltriethoxysilane coupling agent is selected to modify it. DETAILED DESCRIPTION

[0033] The present invention is further described below with reference to the embodiments.

[0034] Example 1

[0035] The method for preparing the polytetrafluoroethylene ultrafine filaments described in this embodiment 1 comprises the following steps:

[0036] (1) cordierite fiber, nano-baryte and anhydrous ethanol are uniformly mixed to prepare a suspension, and then heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane are added and mixed for 68 minutes, and finally a mixture of modified cordierite fiber and nano-baryte is prepared by ball milling, drying and sieving;

[0037] (2) poly(p-phenylene sulfoxide) was mixed with poly(p-phenylene sulfoxide) to prepare a poly(p-phenylene sulfoxide) dispersion, which was then freeze-dried to prepare a pretreated poly(p-phenylene sulfoxide) fiber. Toluene, acetic acid and phenyltriethoxysilane coupling agent were added to the pretreated poly(p-phenylene sulfoxide) fiber, and the mixture was reacted at 73° C. for 7.7 hours. The pretreated poly(p-phenylene sulfoxide) fiber was dried to prepare a modified poly(p-phenylene sulfoxide) fiber.

[0038] (3) mixing polytetrafluoroethylene dispersion resin, a mixture of modified cordierite fiber and nano-barite, modified polyparabenzamide fiber, No. 5 aviation kerosene and Isopar M solvent oil, and then sequentially performing aging, pressing, extrusion and calendaring treatments to prepare a modified polytetrafluoroethylene-based membrane;

[0039] (4) The modified polytetrafluoroethylene based film prepared in step (3) is deoiled at 288° C., then stretched, and cut into polytetrafluoroethylene flat filaments. Finally, the polytetrafluoroethylene flat filaments are heat-drawn, twisted, and heat-set to prepare polytetrafluoroethylene ultrafine filaments.

[0040] in:

[0041] In step (1), the mass ratio of cordierite fiber to nano-baryte and to anhydrous ethanol is 1:25.

[0042] In step (1), the mass ratio of cordierite fiber to nano-baryte is 1:0.7.

[0043] In step (1), the cordierite fiber, nano-barite and anhydrous ethanol are uniformly mixed by stirring at a speed of 500 r / min for 75 min, and then ultrasonically dispersed for 38 min at an ultrasonic power of 50 W.

[0044] In step (1), the mass ratio of heptadecafluorodecyltrimethoxysilane to γ-aminopropyltriethoxysilane is 3:1.

[0045] In step (1), the total mass of heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane accounts for 2.5% of the total mass of cordierite fiber and nano-bite.

[0046] The ball milling, drying and sieving in step (1) specifically comprises ball milling the slurry obtained after mixing in a ball mill for 43 minutes, then drying at 77° C. for 4.5 hours, and finally passing through a 250-mesh sieve.

[0047] In step (2), the mass volume ratio of polyparabenzamide fiber to dimethyl sulfoxide is 1:2.8, expressed in g / mL.

[0048] The mixing in step (2) is stirred at room temperature for 28 hours, and the freeze-drying is freeze-dried at -45°C for 50 hours.

[0049] In step (2), the mass of the phenyltriethoxysilane coupling agent is 2.4% of the mass of the pretreated polyparabenzamide fiber. Acetic acid is added to adjust the pH value of the reaction system to 5. The mass ratio of the pretreated polyparabenzamide fiber to toluene is 1:20.

[0050] The drying temperature in step (2) is 120° C. and the drying time is 3.5 h.

[0051] In step (3), the mass of the mixture of modified cordierite fiber and nano-baryte accounts for 2.5% of the mass of the polytetrafluoroethylene dispersion resin, the mass of the modified polyparabenzamide fiber accounts for 3.9% of the mass of the polytetrafluoroethylene dispersion resin, the mass of No. 5 aviation kerosene accounts for 6% of the mass of the polytetrafluoroethylene dispersion resin, and the mass of Isopar M solvent oil accounts for 18% of the mass of the polytetrafluoroethylene dispersion resin.

[0052] The manufacturer of Isopar M solvent oil in step (3) is ExxonMobil.

[0053] The aging, pressing, extrusion and calendering treatment in step (3) is specifically aging at 67°C for 55 hours, pressing the aging raw material into a columnar blank at a pressure of 5 MPa, and then extruding the columnar blank into a strip, with a compression ratio of 280 and an extrusion speed of 15 m / min. Finally, the extruded strip is pressed into a polytetrafluoroethylene-based film by a calender, the pressing roller temperature is 75°C, and the calendering line speed is 10 m / min.

[0054] In step (4), the stretching temperature is 270°C and the stretching ratio is 3 times.

[0055] The width of the polytetrafluoroethylene flat filament in step (4) is 5 mm.

[0056] The temperature of the hot stretching in step (4) is 375°C and the stretching ratio is 40 times.

[0057] The twisting degree in step (4) is 450 twists / m.

[0058] The temperature of heat setting in step (4) is 388°C.

[0059] Example 2

[0060] The method for preparing the polytetrafluoroethylene ultrafine filaments described in this embodiment 2 comprises the following steps:

[0061] (1) cordierite fiber, nano-baryte and anhydrous ethanol are mixed uniformly to prepare a suspension, and then heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane are added and mixed for 65 minutes, and finally a mixture of modified cordierite fiber and nano-baryte is prepared by ball milling, drying and sieving;

[0062] (2) poly(p-phenylene sulfoxide) was mixed with poly(p-phenylene sulfoxide) to prepare a poly(p-phenylene sulfoxide) dispersion, which was then freeze-dried to prepare a pretreated poly(p-phenylene sulfoxide) fiber. Toluene, acetic acid and phenyltriethoxysilane coupling agent were added to the pretreated poly(p-phenylene sulfoxide) fiber, and the mixture was reacted at 70° C. for 8 h. The pretreated poly(p-phenylene sulfoxide) fiber was dried to prepare a modified poly(p-phenylene sulfoxide) fiber.

[0063] (3) mixing polytetrafluoroethylene dispersion resin, a mixture of modified cordierite fiber and nano-barite, modified polyparabenzamide fiber, No. 5 aviation kerosene and Isopar M solvent oil, and then sequentially performing aging, pressing, extrusion and calendaring treatments to prepare a modified polytetrafluoroethylene-based membrane;

[0064] (4) The modified polytetrafluoroethylene based film prepared in step (3) is deoiled at 290° C., then stretched, and cut into polytetrafluoroethylene flat filaments. Finally, the polytetrafluoroethylene flat filaments are heat-drawn, twisted, and heat-set to prepare polytetrafluoroethylene ultrafine filaments.

[0065] in:

[0066] In step (1), the mass ratio of cordierite fiber to nano-baryte and to anhydrous ethanol is 1:25.

[0067] In step (1), the mass ratio of cordierite fiber to nano-baryte is 1:0.6.

[0068] In step (1), the cordierite fiber, nano-barite and anhydrous ethanol are uniformly mixed, specifically stirred at a speed of 500 r / min for 70 min, and then ultrasonically dispersed for 35 min at an ultrasonic power of 50 W.

[0069] In step (1), the mass ratio of heptadecafluorodecyltrimethoxysilane to γ-aminopropyltriethoxysilane is 3:1.

[0070] In step (1), the total mass of heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane accounts for 2% of the total mass of cordierite fiber and nano-bite.

[0071] The ball milling, drying and sieving in step (1) specifically comprises ball milling the slurry obtained after mixing in a ball mill for 40 minutes, then drying at 75° C. for 4.5 hours, and finally passing through a 250-mesh sieve.

[0072] In step (2), the mass volume ratio of polyparabenzamide fiber to dimethyl sulfoxide is 1:2.8, expressed in g / mL.

[0073] The mixing in step (2) is stirred at room temperature for 28 hours, and the freeze-drying is freeze-dried at -45°C for 50 hours.

[0074] In step (2), the mass of the phenyltriethoxysilane coupling agent is 2.4% of the mass of the pretreated polyparabenzamide fiber. Acetic acid is added to adjust the pH value of the reaction system to 5. The mass ratio of the pretreated polyparabenzamide fiber to toluene is 1:20.

[0075] The drying temperature in step (2) is 120° C. and the drying time is 3.5 h.

[0076] In step (3), the mass of the mixture of modified cordierite fiber and nano-baryte accounts for 2.2% of the mass of the polytetrafluoroethylene dispersion resin, the mass of the modified polyparabenzamide fiber accounts for 4.3% of the mass of the polytetrafluoroethylene dispersion resin, the mass of No. 5 aviation kerosene accounts for 6% of the mass of the polytetrafluoroethylene dispersion resin, and the mass of Isopar M solvent oil accounts for 18% of the mass of the polytetrafluoroethylene dispersion resin.

[0077] The manufacturer of Isopar M solvent oil in step (3) is ExxonMobil.

[0078] The aging, pressing, extrusion and calendering treatment in step (3) is specifically aging at 70°C for 55 hours, pressing the aging raw material into a columnar blank at a pressure of 5 MPa, and then extruding the columnar blank into a strip, with a compression ratio of 280 and an extrusion speed of 15 m / min. Finally, the extruded strip is pressed into a polytetrafluoroethylene-based film by a calender, the pressing roller temperature is 75°C, and the calendering line speed is 10 m / min.

[0079] In step (4), the stretching temperature is 270°C and the stretching ratio is 3 times.

[0080] The width of the polytetrafluoroethylene flat filament in step (4) is 5 mm.

[0081] The temperature of the hot stretching in step (4) is 375°C and the stretching ratio is 40 times.

[0082] The twisting degree in step (4) is 450 twists / m.

[0083] The heat setting temperature in step (4) is 390°C.

[0084] Example 3

[0085] The method for preparing the polytetrafluoroethylene ultrafine filaments described in this embodiment 3 comprises the following steps:

[0086] (1) cordierite fiber, nano-baryte and anhydrous ethanol are mixed uniformly to prepare a suspension, and then heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane are added and mixed for 70 minutes, and finally ball milled, dried and sieved to prepare a mixture of modified cordierite fiber and nano-baryte;

[0087] (2) poly(p-phenylene sulfoxide) was mixed with poly(p-phenylene sulfoxide) to prepare a poly(p-phenylene sulfoxide) dispersion, which was then freeze-dried to prepare a pretreated poly(p-phenylene sulfoxide) fiber. Toluene, acetic acid and phenyltriethoxysilane coupling agent were added to the pretreated poly(p-phenylene sulfoxide) fiber, and the mixture was reacted at 75° C. for 7.5 h. The pretreated poly(p-phenylene sulfoxide) fiber was dried to prepare a modified poly(p-phenylene sulfoxide) fiber.

[0088] (3) mixing polytetrafluoroethylene dispersion resin, a mixture of modified cordierite fiber and nano-barite, modified polyparabenzamide fiber, No. 5 aviation kerosene and Isopar M solvent oil, and then sequentially performing aging, pressing, extrusion and calendaring treatments to prepare a modified polytetrafluoroethylene-based membrane;

[0089] (4) The modified polytetrafluoroethylene based film prepared in step (3) is deoiled at 285° C., then stretched, and cut into polytetrafluoroethylene flat filaments. Finally, the polytetrafluoroethylene flat filaments are heat-drawn, twisted, and heat-set to prepare polytetrafluoroethylene ultrafine filaments.

[0090] in:

[0091] In step (1), the mass ratio of cordierite fiber to nano-baryte and to anhydrous ethanol is 1:25.

[0092] In step (1), the mass ratio of cordierite fiber to nano-baryte is 1:0.8.

[0093] In step (1), the cordierite fiber, nano-barite and anhydrous ethanol are uniformly mixed by stirring at a speed of 500 r / min for 80 min, and then ultrasonically dispersed for 40 min at an ultrasonic power of 50 W.

[0094] In step (1), the mass ratio of heptadecafluorodecyltrimethoxysilane to γ-aminopropyltriethoxysilane is 3:1.

[0095] In step (1), the total mass of heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane accounts for 3% of the total mass of cordierite fiber and nano-bite.

[0096] The ball milling, drying and sieving in step (1) specifically comprises ball milling the slurry obtained after mixing in a ball mill for 45 minutes, then drying at 78° C. for 4.5 hours, and finally passing through a 250-mesh sieve.

[0097] In step (2), the mass volume ratio of polyparabenzamide fiber to dimethyl sulfoxide is 1:2.8, expressed in g / mL.

[0098] The mixing in step (2) is stirred at room temperature for 28 hours, and the freeze-drying is freeze-dried at -45°C for 50 hours.

[0099] In step (2), the mass of the phenyltriethoxysilane coupling agent is 2.4% of the mass of the pretreated polyparabenzamide fiber. Acetic acid is added to adjust the pH value of the reaction system to 5. The mass ratio of the pretreated polyparabenzamide fiber to toluene is 1:20.

[0100] The drying temperature in step (2) is 120° C. and the drying time is 3.5 h.

[0101] In step (3), the mass of the mixture of modified cordierite fiber and nano-baryte accounts for 2.8% of the mass of the polytetrafluoroethylene dispersion resin, the mass of the modified polyparabenzamide fiber accounts for 3.5% of the mass of the polytetrafluoroethylene dispersion resin, the mass of No. 5 aviation kerosene accounts for 6% of the mass of the polytetrafluoroethylene dispersion resin, and the mass of Isopar M solvent oil accounts for 18% of the mass of the polytetrafluoroethylene dispersion resin.

[0102] The manufacturer of Isopar M solvent oil in step (3) is ExxonMobil.

[0103] The aging, pressing, extrusion and calendering treatment in step (3) is specifically aging at 65°C for 55 hours, pressing the aging raw material into a columnar blank at a pressure of 5 MPa, and then extruding the columnar blank into a strip, with a compression ratio of 280 and an extrusion speed of 15 m / min. Finally, the extruded strip is pressed into a polytetrafluoroethylene-based film by a calender, the pressing roller temperature is 75°C, and the calendering line speed is 10 m / min.

[0104] In step (4), the stretching temperature is 270°C and the stretching ratio is 3 times.

[0105] The width of the polytetrafluoroethylene flat filament in step (4) is 5 mm.

[0106] The temperature of the hot stretching in step (4) is 375°C and the stretching ratio is 40 times.

[0107] The twisting degree in step (4) is 450 twists / m.

[0108] The temperature of heat setting in step (4) is 385°C.

[0109] Comparative Example 1

[0110] The method for preparing the polytetrafluoroethylene ultrafine filaments described in this comparative example 1 is the same as that in Example 1, with the only difference being that step (1) is omitted and the mixture of modified cordierite fiber and nano-baryte is not added in step (3); in step (3), the mass of the modified polyparabenzamide fiber accounts for 3.9% of the mass of the polytetrafluoroethylene dispersion resin, the mass of No. 5 aviation kerosene accounts for 6% of the mass of the polytetrafluoroethylene dispersion resin, and the mass of Isopar M solvent oil accounts for 18% of the mass of the polytetrafluoroethylene dispersion resin.

[0111] Comparative Example 2

[0112] The method for preparing the polytetrafluoroethylene ultrafine filaments described in this comparative example 2 is the same as that in Example 1, with the only difference being that step (2) is omitted and modified polyparabenzamide fiber is not added in step (3); in step (3), the mass of the mixture of modified cordierite fiber and nano-baryte accounts for 2.5% of the mass of the polytetrafluoroethylene dispersion resin, the mass of No. 5 aviation kerosene accounts for 6% of the mass of the polytetrafluoroethylene dispersion resin, and the mass of Isopar M solvent oil accounts for 18% of the mass of the polytetrafluoroethylene dispersion resin.

[0113] The performance test of the polytetrafluoroethylene ultrafine filaments with a fineness of 80 denier prepared in Examples 1-3 and Comparative Examples 1-2 was carried out, and the results are shown in Table 1 below:

[0114] Table 1 Performance test results of polytetrafluoroethylene ultrafine filaments

[0115]

[0116] It can be seen from Table 1 that the breaking strength of the polytetrafluoroethylene superfine filaments prepared in Examples 1-3 is greater than that of the polytetrafluoroethylene superfine filaments prepared in Comparative Examples 1-3, and the breaking elongation and the unevenness of the strands are less than those of the polytetrafluoroethylene superfine filaments prepared in Comparative Examples 1-3. Comparative Example 1 does not add the mixture of modified cordierite fiber and nano-baryte when preparing the polytetrafluoroethylene superfine filaments, and Comparative Example 2 does not add modified polyparabenzamide fiber when preparing the polytetrafluoroethylene superfine filaments, both of which lead to a significant decrease in the performance of the prepared polytetrafluoroethylene superfine filaments.

Claims

1. A method for preparing polytetrafluoroethylene ultrafine filaments, characterized in that: It consists of the following steps: (1) cordierite fiber, nano-baryte and anhydrous ethanol are uniformly mixed to prepare a suspension, and then heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane are added and mixed for 65-70 minutes, and finally ball milled, dried and sieved to prepare a mixture of modified cordierite fiber and nano-baryte; (2) mixing poly(p-phenylene sulfoxide) with dimethyl sulfoxide to prepare a poly(p-phenylene sulfoxide) fiber dispersion, and then freeze-drying the mixture to prepare a pretreated poly(p-phenylene sulfoxide) fiber, adding toluene, acetic acid and phenyltriethoxysilane coupling agent to the pretreated poly(p-phenylene sulfoxide) fiber, reacting the mixture at 70-75° C. for 7.5-8 hours, and finally drying the mixture to prepare a modified poly(p-phenylene sulfoxide) fiber; (3) mixing polytetrafluoroethylene dispersion resin, a mixture of modified cordierite fiber and nano-barite, modified polyparabenzamide fiber, No. 5 aviation kerosene and Isopar M solvent oil, and then sequentially performing aging, pressing, extrusion and calendaring treatments to prepare a modified polytetrafluoroethylene-based membrane; (4) The modified polytetrafluoroethylene based film prepared in step (3) is deoiled at 285-290° C., then stretched, and cut into polytetrafluoroethylene flat filaments. Finally, the polytetrafluoroethylene flat filaments are heat-drawn, twisted, and heat-set to prepare polytetrafluoroethylene ultrafine filaments.

2. The method for preparing polytetrafluoroethylene ultrafine filaments according to claim 1, characterized in that: In step (1), the mass ratio of cordierite fiber to nano-baryte is 1:0.6-0.8; In step (1), the cordierite fiber, nano-baryte and anhydrous ethanol are uniformly mixed, specifically stirred at a speed of 500 r / min for 70-80 min, and then ultrasonically dispersed for 35-40 min at an ultrasonic power of 50 W; In step (1), the mass ratio of heptadecafluorodecyltrimethoxysilane to γ-aminopropyltriethoxysilane is 3:1; In step (1), the total mass of heptadecafluorodecyltrimethoxysilane and γ-aminopropyltriethoxysilane accounts for 2-3% of the total mass of cordierite fiber and nano-bite.

3. The method for preparing polytetrafluoroethylene ultrafine filaments according to claim 1, characterized in that: The ball milling, drying and sieving in step (1) specifically comprises ball milling the slurry obtained after mixing in a ball mill for 40-45 minutes, then drying at 75-78° C. for 4.5 hours, and finally passing through a 250 mesh sieve; In step (1), the mass ratio of cordierite fiber to nano-baryte and to anhydrous ethanol is 1:

25.

4. The method for preparing ultra-fine polytetrafluoroethylene filaments according to claim 1, characterized in that: In step (2), the mass volume ratio of polyparabenzamide fiber to dimethyl sulfoxide is 1:2.8, expressed in g / mL; The mixing in step (2) is stirred at room temperature for 28 hours, and the freeze-drying is freeze-dried at -45°C for 50 hours.

5. The method for preparing polytetrafluoroethylene ultrafine filaments according to claim 1, characterized in that: In step (2), the mass of the phenyltriethoxysilane coupling agent is 2.4% of the mass of the pretreated polyparabenzamide fiber, acetic acid is added to adjust the pH value of the reaction system to 5, and the mass ratio of the pretreated polyparabenzamide fiber to toluene is 1:20; The drying temperature in step (2) is 120° C. and the drying time is 3.5 h.

6. The method for preparing ultra-fine polytetrafluoroethylene filaments according to claim 1, characterized in that: In step (3), the mass of the mixture of modified cordierite fiber and nano-baryte accounts for 2.2-2.8% of the mass of the polytetrafluoroethylene dispersion resin, the mass of the modified polyparabenzamide fiber accounts for 3.5-4.3% of the mass of the polytetrafluoroethylene dispersion resin, the mass of No. 5 aviation kerosene accounts for 6% of the mass of the polytetrafluoroethylene dispersion resin, and the mass of Isopar M solvent oil accounts for 18% of the mass of the polytetrafluoroethylene dispersion resin.

7. The method for preparing polytetrafluoroethylene ultrafine filaments according to claim 1, characterized in that: The aging, pressing, extrusion and calendering treatment in step (3) is specifically aging at 65-70°C for 55 hours, pressing the aging raw material into a columnar blank at a pressure of 5 MPa, and then extruding the columnar blank into a strip, with a compression ratio of 280 and an extrusion speed of 15 m / min. Finally, the extruded strip is pressed into a polytetrafluoroethylene-based film by a calender, the pressing roller temperature is 75°C, and the calendering line speed is 10 m / min.

8. The method for preparing polytetrafluoroethylene ultrafine filaments according to claim 1, characterized in that: In step (4), the stretching temperature is 270°C and the stretching ratio is 3 times; The width of the polytetrafluoroethylene flat filament in step (4) is 5 mm.

9. The method for preparing polytetrafluoroethylene ultrafine filaments according to claim 1, characterized in that: The temperature of the hot stretching in step (4) is 375°C and the stretching ratio is 40 times; The twisting degree in step (4) is 450 twists / m.

10. The method for preparing ultra-fine polytetrafluoroethylene filaments according to claim 1, characterized in that: The temperature of the heat setting in step (4) is 385-390°C.

Citation Information

Patent Citations

  • High strength polytetrafluoroethylene fiber and process for producing same

    CN1966786A

  • Polytetrafluoroethylene / barium sulfate composite and preparation method thereof

    CN106084588A

  • Polytetrafluoroethylene superfine fiber

    CN106283249A